New directions in tropical Asian architecture - Goad, Philip; Pieris, Anoma (North Clarendon, VT : Tuttle Publishing, 2005)
"The rationale for an examination of new directions in tropical Asian architecture is not hard to find. First and foremost, it is simply overdue. Secondly, this book represents one step in opening up the region to greater scrutiny, to a greater embrace of its complexity. It provides documentation that will stimulate self-reflexive analysis, rather than analysis that is reliant on Western benchmarks of what is deemed to be good. And thirdly, the discourse which has recently arisen from this region has been mired in stereotype, and criticism has foundered on a singular focus on the 'tropical house' or 'tropical resort'." - Philip Goad "It is tropical Asia's ability to transform modern imperatives to suit its own ideological frameworks that makes its architecture exciting and different. In the post-national era, the new Asian citizen has left the dappled light of the tropical verandah for the reflected light of the shopping mall, the muted glow of the video arcade and the neon flicker of the city street. But how have the region's architects begun to programme, conceptualise, and design for this future? The works in this book go far in answering this question'. -- Anoma Pieris
New directions in tropical Asian architecture -- The search for tropical indentities: a critical history -- Kerry Hill -- Kanika R'Kul -- Cheong Yew Kuan -- SCDA -- Eko Prawoto -- Rahul Mehrotra -- W Architects -- Anura Ratnavibushana -- Kevin Low -- Andra Matin Architect -- WOHA.
Keywords: ARCHITECTURE, TROPICAL -- ASIA -- 21ST CENTURY -- CATALOGS